Islamic Jurisprudence of Minorities (Fiqh al-Aqalliyyat): The Case of the Palestinian Muslim Minority in Israel. Issue 2 (2nd April 2016) - Mustafa, Mohanad; Agbaria, Ayman K.
Abstract: This article examines the doctrine of Jurisprudence of Muslim Minorities (Fiqh al-Aqalliyyat) in the context of the Palestinian Muslim community in Israel. The first part discusses the origins and goals of Fiqh al-Aqalliyyat. After outlining the particular historical and political context of the Palestinian minority in Israel, the article focuses on the ethno-religious political mobilization developed by the Muslim community vis-à-vis the state's strategies of control and domination, and points out the difficulties involved in the application of Fiqh al-Aqalliyyat, as used in "Western" states, for the reality that Muslims face in Israel. The article suggests a vigilant approach toward the Jurisprudence of Minorities, as we argue that, when applying it in this context of the Muslim community in Israel, this doctrine has two substantial limitations. The first is theoretical and it concerns the doctrine's current incapability to distinguish between different types of minorities, as well as failing to recognize a difference between various political regimes and societal lives that might be inherently less or more accommodating or even hostile to minorities, and Muslim minority communities in particular. The second limitation relates to the political dimension and the lack of consideration for the status of the Palestinian minority as an indigenous and national minority and not an immigrant minority. Their status as national minorities, at times also as indigenous peoples, who are perceived as entitled to group-based "self-government rights", poses a serious challenge to this doctrine's scope and viability.